Formulasi dan evaluasi gel Lidah buaya (Aloe vera Linn) sebagai pelembab kulit dengan penggunaan carbopol sebagai gelling agent - Benni Iskandar; Zyzy Permata Dian; Fitri Renovita; Leny Leny (Health Sciences and Pharmacy Journal, 2021)
Indonesia is a rich country in natural resources. Aloe vera (Aloe vera Linn) is a natural resource that has the potential to be developed. Aloe vera (Aloe vera Linn) has been shown to have a function as a skin moisturizer. The purpose of this study was to determine whether the aloe vera gel formulation has fulfilled the evaluation requirements in accordance with existing standards. This research was conducted by making aloe vera gel preparations in two formulas with carbopol variance, namely each with a concentration of 0,5% (F1), 1% (F2). Evaluation of gel preparations includes organoleptic, pH measurement, stability check at room temperature and cold temperature, spread-ability test, adhesion test, homogeneity test, and irritation test. The study was conducted for 2 months for stability, every week for pH measurement and at week 1 and week 8 on the dispersion and gel-ability, while the homogeneity and irritation tests were carried out after completing the formulation. The results showed that the evaluations that have fulfilled the requirements were organoleptic evaluation, stability at room temperature and cold temperature, homogeneity, and irritation. The evaluations that did not meet the requirements were the pH measurements at F1 and the spread-ability in both formulas.